Pengembangan Aktivitas Masjid dalam Meningkatkan Kesadaran Masyarakat Desa Bukit Peninjauan 1 - Wiko Pibi Hardian; Clara Sahfitri; Irma Wulan Tari; Ayu Marisa Utami; Khoirun Nur Fitri; Diya Permata Sari; Teguh Rahmat Hidayat; Anisa Nurhasanah; Rahma Suci Agustin; Mixchel Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to launch the development of mosque activities in Bukit Peninjauan 1 Village, Sukaraja District, Seluma Regency, in order to increase public awareness of the function of mosques as centers of social and religious activities. The research method used is qualitative with a case study approach, which includes in-depth interviews, focus group discussions (FGD), participant observation, and documentation. The research results show that people's perception of mosques is still limited to their main worship function, with low awareness of the potential of mosques as educational, social and economic centers. The level of community participation in non-worship activities is also relatively low, with the majority of the community only active in congregational prayers and routine recitation activities. Some of the main challenges identified include limited resources, lack of community support, and inadequate facilities. This research concludes that to optimize the role of mosques as multifunctional activity centers, more intensive outreach efforts are needed, program development that is relevant to community needs, as well as collaborative support from various parties. With these steps, the Al-Amin Mosque in Bukit Peninjauan 1 Village has the potential to become the center of a more active and productive community life.